Avaliação de serviço de saúde em HIV/AIDS: a perspectiva dos usuários - Dossena, Laura Olinto (Universidade do Vale do Rio dos Sinos, 2011)
This study was the assessment by a group of users, a service facility specializing in HIV / AIDS in Porto Alegre, RS, relating the perceptions of the group with the dimensions of the electronic questionnaire for the assessment of STD / AIDS and Viral Hepatitis - Qualiaids from the perspective of integrality and humanization. For data processing we used the technique of focus groups and thematic analysis. The results, revealed the importance of host and access elements in the assessment made by users of the service, influencing the establishment of a rapport, adherence to treatment and preference for the service. Has been found the user satisfaction in using the service. The pressure of growing demand negatively interferes with the user-service relationship. The organization of health practices, as well as detailed studies on the subject, are needed to mitigate the prejudice of people living with HIV / AIDS. This work shows the relevance of considering the user's participation in evaluations of health services to qualify for assistance.
Keywords: Instituições de saúde; Recursos Humanos e serviços; Garantia da qualidade dos cuidados de saúde; Síndrome de Imunodeficiência Adquirida.; Health Care Facilities; Manpower and services; Quality assurance; Health care; Acquired Immunodeficiency Syndrome; ACCNPQ::Ciências da Saúde::Saúde Coletiva